Legal Responsibility of Doctors in the Use of Neuralink Technology: An Indonesian Health Law Perspective - Mangesti, Yovita Arie; ., Sartono (Journal of Ecohumanism, 2025)
Neuralink technology is a groundbreaking innovation in the field of healthcare, utilizing Brain-Computer Interface (BCI) to aid patients with neurological disorders, enhance rehabilitation capabilities, and support artificial intelligence-based medical advancements. This study analyzes the legal responsibility of doctors using Neuralink technology under Indonesian health law, considering statutory and conceptual approaches. The research highlights the regulatory framework, professional responsibilities, and ethical considerations in adopting this technology within Indonesia’s healthcare system. This study employs a normative legal research methodology, focusing on statutory analysis, legal doctrines, and comparative legal studies. It examines Indonesia’s current health laws, professional liability standards, and international regulatory frameworks to provide a comprehensive understanding of the legal implications surrounding Neuralink. The results indicate significant gaps in Indonesia’s regulatory landscape, necessitating tailored legal provisions to address emerging challenges in AI-driven medical interventions. The findings underscore the need for clear liability guidelines for medical practitioners, enhanced informed consent mechanisms, and robust patient protection policies. Additionally, economic and ethical considerations, including equitable access and cognitive enhancement concerns, are discussed to highlight broader societal implications. The study concludes that interdisciplinary collaboration between legal experts, medical professionals, and policymakers is essential to developing a balanced regulatory approach for Neuralink technology in Indonesia.